PERAN JENIS DAN KONSENTRASI KOAGULAN PADA KARAKTERISTIK TAHU DAN TINGKAT PENERIMAAN KONSUMEN - Widjajaseputra, Anna Ingani; Widyastuti, Theresia Endang Widoeri; Suprijono, Maria Matoetina; Trisnawati, Chatarina Yayuk (Jurnal Teknologi Pangan dan Gizi, 2020)
The supply of soybean varieties with certain specification is still a problem for the tofu industry, so it needs to be resolved, one of which is the selection of capable coagulant. This research aimed to study the effect of different of coagulants (CaSO4 , CaCl2 , and MgCl2) and the concentration [0.4 % ( w / v ) and 0.5 % ( w / v )] to the characteristics of fresh tofu and its consumer acceptance.The tofu characteristics especially water holding capacity and gel strength could determine the tofu yield and texture parameters. Based on the research result, it showed that different types of coagulant have specific characteristics such as rate of coagulation and water entrapment capacity. Coagulant concentration of 0.5 % on all types of salt coagulant was used in this study showed the effect of decreasing the water holding capacity of the curd. Salt concentration of 0.5 % provided more formed cross-link so that the structure to be too compact. Higher protein content was obtained at concentration of 0.5 % for the same type of coagulant, but it was not followed by significant difference of texture. Based on sensory evaluation data, it can be concluded that CaSO4 0.4 % produced the most preferred product. The usage of MgCl2 0.4% can be recommended beside of CaSO4 0.4 %.